A case study of the Singapore SkillsFuture Credit scheme: preliminary insights for making lifelong learning policy more effective. Issue 2 (4th May 2021) - Kim, Soojin; Chen, Zheng Wei; Tan, Jian Qi (Gerald); Mussagulova, Assel
ABSTRACT: In pursuit of sustainable, human capital-centric growth, Singapore initiated a lifelong learning policy of SkillsFuture Credit (SFC) which enables citizens to advance their skills in an autonomous and flexible manner. However, the results so far indicate that the SFC outcomes are not aligned with the policy goals it set out to achieve, as the participation rates remain subpar, and program implementation is dotted with fraudulent claims. This study aims to gauge the effectiveness of SFC both in achieving its primary policy goals and an overarching objective of building a culture of lifelong learning in Singapore. In doing so, this study relies on perspectives of the main stakeholders of SFC using the framework of policy feedback and policy-learning effects. The findings show that while most respondents are satisfied with the SFC, low participation rates are largely driven by structural barriers of time and financial cost. In addition, there exists a mismatch between the government-driven pragmatism rhetoric in lifelong learning and the personal aspirations of respondents towards self-development. Policymakers may benefit from the findings of this research by recalibrating their approach through investing in more diverse, high-quality courses, ensuring the value of the course certificates for employability, and improving the outreach efforts.